Review on Development of Ice-Ship - Koto, J.; Afrizal, Efi (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
In the early stage, sailing by ships at North and Artic Seas should be able to break ice which is commonly called as ice-breakers. Dimensions of the ice breakers were not big enough to be used as a cargo or large carrier. As the demand to merchant ships has been increased, the development technologies on hull form design and propulsion system for ice-going ship have been improved gradually. This paper discussed historical ice ships, the development of ships in ice such as ice breaker, double acting ship and offshore floating by taken two parameters into account which is hull form design and propulsion system.